POTENSI WILAYAH TERDAMPAK KERUNTUHAN BENDUNGAN MATENGGENG DI SUNGAI CIJOLANG - Utomo, Bagus Prio; Rahardjo, Adam Pramudji; Legono, Djoko (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2019)
Matenggeng Dam, which plans to be built on the Cijolang River, is a multifunctional dam that has many benefits for communities to irrigate irrigation, raw water, flood control, power generation and tourism. Besides having many benefits, dam construction also keeps very high potential hazards. One of the potential hazards that can occur is the dam breach caused by a crack due to water going over the crest (overtopping) or fracture due to seepage in the body of the weir (piping). Dam breach will cause very big flood so it can cause casualties and damage to property. Using the HEC-RAS 5.0.3 program, we found that in the overtopping scenario, the spillway dimension was still able to pass the maximum discharge (QPMF) of 9.067 m3 /s so that the water did not reach the crest. In the piping scenario, estimated that the extent of inundation reaches 17.568 ha and will inundate 92 villages, 416 km of roads, and 169 public facilities. Over half of the flooded areas are categorized as high to extreme hazards with rice fields are the areas that fall into the category most.